Therapeutic in vitro and in vivo approach of influenza virus infection by simultaneous reduction of virus titre and cytokine expression through inhibition of virus-induced NF-kappaB and Raf-MEK-ERK activation - Pinto, Ana Ruth Jorge Portugal Machado; Justus Liebig University Giessen (My University, 2008)
Influenza A virus (IAV) infection can cause severe pneumonia and lead to acute respiratory distress syndrome and ultimately death. Despite damage by viral replication, imbalanced production of anti-viral cytokines ( cytokine storm ) resulting in inflammation can also lead to severe lung destruction.Therapeutics as vaccines and anti-viral drugs target components of the virus itself resulting in resistant variants. Therefore new therapeutic measures are urgently needed. IAV has been shown to activate the NF-kappaB and MAPK (Raf/EK/ERK) signalling pathway. These pathways seem to have both pro- and anti-viral effects, by promoting nuclear export of the viral genome and by inducing expression of anti-viral pro-inflammatory factors. Therefore it was postulated that the inhibition of these signalling pathways will simultaneously reduce virus replication as well as modulate cytokine production without affecting host defence. Using specific IKK- (Bay-11-7082) and MEK- (U0126) inhibitors at non-toxic concentrations, I analysed the effect of NF-kappaB and MAPK pathway inhibition on propagation of a highly pathogenic avian influenza virus (strain A/FPV/Bratislava/79, H7N7) and a human influenza virus (strain A/PR/8/34, H1N1) and the virus-induced cytokine induction in infected human lung epithelia cells (A549) and mice primary alveolar epithelial cells (AECs), in vitro. Experiments were also performed in an in vivo mouse model for proof of principle applying the above inhibitors and the A/PR/8/34 virus for infection. Results show, (1) by western blot and transcription factor assay that both pathways (NF-kappaB and MAPK) are activated upon IAV infection in A549 cells; (2) that both inhibitors (IKK-, MEK-inhibitor), used at non-toxic concentrations, lead to decrease in signalling, virus titres (FFU assay) and (3) reduced cytokine expression (multiplex cytokine assay and ELISA), in vitro (A549 and AECs) as well as in vivo (mice). I also observed differences in the virus-induced (FPV and PR8) cytokine release when comparing different cell types (A549, AECs) as well as in the mouse model. The results demonstrate that inhibition of NF-kappaB and Raf/MEK/ERK pathway can be used to simultaneously reduce virus titres and modulate pro-inflammatory cytokine expression in vitro as well as in vivo. This could be of importance for future therapeutic strategies to treat influenza pneumonia and virus induced Cytokine Storm .

Eine Infektion mit dem Influenza A virus (IAV) kann schwere Pneumonien verursachen, die zum akuten Atemnotsyndrom und schließlich zum Tod führen können. Neben der Schädigung durch die virale Replikation, kann auch die in einer überschießende Entzündung resultierende, ungeregelte Produktion von anti-viralen Zytokinen ( Zytokinsturm ), zu einer ernsthaften Schädigung der Lunge führen. Impfstoffe und anti-virale Substanzen als Therapeutika richten sich in der Regel gegen bestimmte virale Funktionen und Virusbestandteile und führen somit schnell zu Resistenzen. Daher sind neue therapeutische Möglichkeiten dringend notwendig. Es konnte bereits nachgewiesen werden, dass IAV den NF-kappaB und den MAPK (Raf/MEK/ERK) Signalweg aktivieren. Diese Signalwege scheinen beide, durch die gleichzeitige Förderung des Kernexports des viralen Genoms und der Expressionsregulation von anti-viralen pro-inflammatorischen Faktoren, pro-und anti-virale Effekte zu besitzen. Daher wurde postuliert, dass durch die Hemmung dieser Signalwege sowohl die Virusvermehrung reduziert werden kann, als auch die Zytokinproduktion moduliert werden kann bei gleichzeitigen Erhalt der Wirstabwehr. Unter Verwendung spezifischer Inhibitoren beider Signalwege (IKK-Inhibitor: Bay-11-7082, MEK-Inhibitor: U0126) in nicht-toxischen Konzentrationen analysierte ich in vitro den Effekt der NF-kappaB- und MAPK-Signalwegsinhibition in Bezug auf die Vermehrung, eines hochpathogenen aviärern Influenzavirus (HPAIV, Stamm A/FPV/Bratislava/79, H7N7) und eines humanen Influenzavirus (Stamm A/PR/8/34, H1N1), sowie die Zytokininduktion in infizierten humanen Lungenepithelzellen (A549) und alveolären primären Mäuseepithelzellen (AECs). Auch wurden zur Bestätigung der Hypothese in einem Modelorganismus diese Experimente unter Verwendung der oben genannten Inhibitoren und des A/PR/8/34 Virus in einem Mausmodell in vivo durchgeführt. Die Resultate zeigten, dass (1) beide Signalwege (NF-kappaB und MAPK) durch die IAV Infektion von A549-Zellen aktiviert werden nachgewiesen durch Westernblot-Analysen und Messung der Transkriptionsfaktor-Aktivierung, (2) beide Inhibitoren (IKK-, MEK-Inhibitor) unter Verwendung in nicht-toxischer Konzentrationen zur Verringerung des Virustiters führen (FFU-Assay) und (3) die Zytokinexpression ( multiplex cytokine assay und ELISA) in vitro (A549 und AECs), sowie in vivo (Mausmodel) verringert ist. Dabei konnte gezeigt werden, dass die Zytokininduktion abhängig ist vom (1) Zellmodel (A549 oder AECs) oder Mausmodel und (2) vom Virusstamm (FPV oder PR8) Die Resultate demonstrieren, dass die Inhibition der NF-kappaB und Raf/MEK/ERK-Signalwege dazu verwendet werden können gleichzeitig Virustiter zu reduzieren und pro-inflammatorische Zytokinexpression in vitro, sowie in vivo zu beeinflussen. Dies könnte zukünftig für die Behandlung von Influenzapneumonien im Bezug auf die Hemmung der Virusvermehrung und Modulation der virusinduzierten Zytokinausschüttung von großer Bedeutung sein.
Therapeutische in vitro und in vivo-Annäherung der Grippe-Virus-Infektion durch die gleichzeitige Verminderung des Virustiters und des Zytokinausdrucks durch die Hemmung der, durch das Virus veranlassten NF-kappaB und Raf-MEK-ERK Aktivierung
Keywords: ddc:610